Cancer predisposing syndromes in childhood and adolescence pose several challenges necessitating interdisciplinary care in dedicated programs - Kaffai, Stefanie; Angelova-Toshkin, Daniela; Weins, Andreas B.; Ickinger, Sonja; Steinke-Lange, Verena; Vollert, Kurt; Frühwald, Michael C.; Kuhlen, Michaela (Frontiers in Pediatrics, 2024)
Introduction: Genetic disposition is a major etiologic factor in childhood cancer. More than 100 cancer predisposing syndromes (CPS) are known. Surveillance protocols seek to mitigate morbidity and mortality. To implement recommendations in patient care and to ascertain that the constant gain of knowledge forces its way into practice specific pediatric CPS programs were established.Patients and methods: We retrospectively analyzed data on children, adolescents, and young adults referred to our pediatric CPS program between